Notas del instructor para el estudio de caso Introduccion de una nueva variedad de frijol en La Merced - Herpen, D. van (International Center for Tropical Agriculture, 1991)
Instructions (general teaching notes, case study instruction), on how to apply the exercise on the case study introduction of a new bean var. in La Merced, Colombia, are given. An example of case study analysis is also provided. (CIAT)